2015
DOI: 10.4038/jas.v10i1.8042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pretreatments on quality of minimally processed cooking banana variety alukesel(Musa acuminata × Musa balbisiana, ABB group)

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…This may be possible as ascorbic acid can act as an intermediate in the metabolism and the growth rate of microorganisms, which can lead to slight increase in their proliferation. Sodium metabisulphite ( at 2 %) did not display antimicrobial effect as TPC increased after 7 days of storage, although the same treatment was relatively effective in controlling browning of fresh cut Alukesel as reported by Siriwardana et al, (2015).…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…This may be possible as ascorbic acid can act as an intermediate in the metabolism and the growth rate of microorganisms, which can lead to slight increase in their proliferation. Sodium metabisulphite ( at 2 %) did not display antimicrobial effect as TPC increased after 7 days of storage, although the same treatment was relatively effective in controlling browning of fresh cut Alukesel as reported by Siriwardana et al, (2015).…”
Section: Discussionmentioning
confidence: 51%
“…It was also evident that the lower concentration of citric acid was less effective in controlling the microbial growth. According to a recent publication by our research group, it was reported that 3% citric acid pretreatment effectively controlled browning and maintained acceptable quality in fresh cut Alukesel (Siriwardana et al, 2015). Similarly, Daranagama et al, (2012) reported 4.93 log 10 CFU/g value for TPC for fresh cut ambarella (Spondias dulcis) and pineapple together as a mixed load, after pretreating with 1% citric acid and storing at 5-7 0 C for seven days.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…They observed that KMS at 0.2% and combination of KMS and AA were most effective in control of browning. Siriwardana et al, (2015) reported that sodium metabisulphite most effectively controlled the browning of sliced banana. The control of browning could be due to oxidative nature of sulphites and their derivatives (sulfur dioxide, sulphite, bisulphite and metabisulphite) which act as color stabilizer.…”
Section: Browning Indexmentioning
confidence: 99%